2006
DOI: 10.1111/j.1365-2869.2006.00525.x
|View full text |Cite
|
Sign up to set email alerts
|

TV exposure associated with sleep disturbances in 5‐ to 6‐year‐old children

Abstract: SUMMARY The aim of this study was to investigate the effects of various forms of TV exposure on the quality of children's sleep. In this randomized population-based survey questionnaires concerning TV viewing, sleep disturbances, and psychiatric symptoms were administered to 321 parents of children aged 5-6 years. Sleep disturbance scores were the main outcome measures. Active TV viewing and passive TV exposure were related to sleeping difficulties, especially sleep-wake transition disorders and overall sleep … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

12
98
3
12

Year Published

2008
2008
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 128 publications
(125 citation statements)
references
References 34 publications
12
98
3
12
Order By: Relevance
“…The primary outcome dichotomized the sleep scale at 0 to 1 (59% at baseline) versus 2 to 10 (41%), so that children were defined as having "any sleep problem" if the parent answered that at least 1 sleep problem occurred 5 to 7 days per week, or at least 2 sleep problems occurred 2 to 4 days per week. The sleep measures were collected at baseline and each follow-up time point (6,12, and 18 months after beginning the intervention).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The primary outcome dichotomized the sleep scale at 0 to 1 (59% at baseline) versus 2 to 10 (41%), so that children were defined as having "any sleep problem" if the parent answered that at least 1 sleep problem occurred 5 to 7 days per week, or at least 2 sleep problems occurred 2 to 4 days per week. The sleep measures were collected at baseline and each follow-up time point (6,12, and 18 months after beginning the intervention).…”
Section: Discussionmentioning
confidence: 99%
“…Although this finding has been consistently replicated with high levels of use, bedtime use, and violent or frightening media content, [1][2][3][4][5][6][7] effects have been observed across cultures and in all media formats (television, 6,[8][9][10] video games, [10][11][12] and computers 11,13,14 ) and across the age spectrum, including preschoolers, 2,7-9 school-aged children, 1,[3][4][5][6] and adolescents and adults. [13][14][15] Much of the existing research linking media use to child sleep problems has been crosssectional, however, raising the possibility that the causality is reversed; that is, that sleep problems are leading to increased media use, evening media use, and exposure to violent media content, rather than the other way around.…”
mentioning
confidence: 96%
“…A study found in the literature 31 , related active as well as passive exposition to television, as a facilitating factor for the appearance of SD. This same study showed that the type of programming to which that child is exposed, also influences his/her patterns of sleep.…”
Section: Discussionmentioning
confidence: 99%
“…Laikas, praleistas prie ekranų, siejamas su ilgesne užmigimo ir trumpesne miego trukme bei miego sutrikimais [7][8][9]. Manoma, kad ryški ir nenatūrali įrenginių skleidžiama šviesa slopina cirkadinio ritmo hormono melatonino gamybą kankorežinėje liaukoje [10,11]. Antra, daugiau laiko prie ekranų praleidžiantys vaikai labiau rizikuoja turėti antsvorį, tai siejant su mažesniu šių vaikų fiziniu aktyvumu [12][13][14].…”
unclassified
“…Ypač šiuo požiūriu reikšmingas gali būti TV kaip "fonas", arba kai TV žiūri tėvai, kiti šeimos nariai vaikui esant šalia. Kadangi šio amžiaus vaikai dar negeba atsirinkti, kas jiems įdomu, o kas ne, be to, greitai besikeičiantys, ryškūs vaizdai bei garsai prikausto jų dėmesį, kai kurių tyrimų duomenimis, būtent foninis IT naudojimas (pvz., buvimas šalia IT naudojančių ar TV žiūrinčių tėvų) gali turėti netgi daugiau žalos mažų vaikų sveikatai, nei aktyvus [4,11,21]. Be to, daugiau laiko prie ekranų leidžiantys tėvai daugiau leidžia būti prie ekranų ir vaikams [21].…”
unclassified